Sex Differences in the Primary Prevention of Cardiovascular Diseases in a Dutch Primary Care Setting - Pauline A. J. Kiss; Alicia Uijl; Estefania Betancur; Annemarijn R. de Boer; Diederick E. Grobbee; Monika Hollander; Charlotte N. Onland-Moret; Miriam C. J. M. Sturkenboom; Sanne A. E. Peters (Ubiquity Press, 2024)
Background: Sex differences in the primary prevention of cardiovascular diseases (CVD) have been shown, but the evidence is mixed and fragmented. In this study, we assessed sex differences in cardiovascular risk factors assessment, risk factor levels, treatment, and meeting of treatment targets, within a Dutch primary care setting. Methods: Data were obtained from individuals aged 40 to 70 years old, without prior CVD, registered during the entire year in 2018 at one of the 51 general practices participating in the Julius General Practitioner's Network (JGPN). History of CVD was defined based on the International Classification of Primary Care (ICPC). Linear and Poisson regressions were used to investigate sex differences in risk factor assessment, risk factor levels, treatment, and meeting of treatment targets. Results: We included 83,903 individuals (50% women). With the exception of glycated hemoglobin (HbA1c), all risk factors for CVD were more often measured in women than in men. Lipid measurements and body mass index values were higher in women, while blood pressure (BP) and HbA1c levels were higher in men, along with estimated glomerular filtration rate (eGFR) levels. Among individuals with elevated BP or cholesterol levels, no sex difference was observed in the prescription of antihypertensive medications (RR 1.00, 95% CI: 0.94-1.06) but women were less likely than men to receive lipid-lowering medications (RR 0.87, 95% CI: 0.79-0.95). Among treated individuals, women were more likely than men to meet adequate levels of blood pressure (RR 1.17, 95% CI: 1.09-1.25) and less likely to meet target levels of cholesterol (RR 0.90, 95% CI: 0.83-0.98). Conclusion: While women were more likely to have their CVD risk factors measured, they were less likely to be prescribed lipid-lowering medications and to meet target levels. When treated, men were less likely to achieve adequate blood pressure control.